RETRACTED: Astragali Radix Isoflavones Synergistically Alleviate Cerebral Ischemia and Reperfusion Injury Via Activating Estrogen Receptor-PI3K-Akt Signaling Pathway - Gu, Yong; Chen, Xi; Fu, Shuping; Liu, Wenlan; Wang, Qi; Liu, Ke-Jian; Shen, Jiangang (Frontiers in Pharmacology, 2021)
Isoflavones are major neuroprotective components of a medicinal herb Astragali Radix, against cerebral ischemia-reperfusion injury but the mechanisms of neuroprotection remain unclear. Calycosin and formononetin are two major AR isoflavones while daidzein is the metabolite of formononetin after absorption. Herein, we aim to investigate the synergistic neuroprotective effects of those isoflavones of Astragali Radix against cerebral ischemia-reperfusion injury. Calycosin, formononetin and daidzein were organized with different combinations whose effects observed in both in vitro and in vivo experimental models. In the in vitro study, primary cultured neurons were subjected to oxygen-glucose deprivation plus reoxygenation (OGD/RO) or l-glutamate treatment. In the in vivo study, rats were subjected to middle cerebral artery occlusion to induce cerebral ischemia and reperfusion. All three isoflavones pre-treatment alone decreased brain infarct volume and improved neurological deficits in rats, and dose-dependently attenuated neural death induced by l-glutamate treatment and OGD/RO in cultured neurons. Interestingly, the combined formulas of those isoflavones revealed synergistically activated estrogen receptor (estrogen receptors)-PI3K-Akt signaling pathway. Using ER antagonist and phosphatidylinositol 3-kinase (PI3K) inhibitor blocked the neuroprotective effects of those isoflavones. In conclusion, isoflavones could synergistically alleviate cerebral ischemia-reperfusion injury via activating ER-PI3K-Akt pathway.